Environmentally Friendly Coastal Protection Proceedings of the NATO Advanced Research Workshop on Environmentally Friendly Coastal Protection Structures Varna, Bulgaria 25-27 May 2004 - Zimmermann, Claus; Dean, Robert G.; Penchev, Valeri; Verhagen, Henk Jan.; SpringerLink (Online service) (Dordrecht : Springer Netherlands, 2005)
Coast lines have been and still are the central lines of civilization around the world with still increasing pressure from both sides - the hinterland and the sea - with all its foreseeable and unforeseeable impacts by means of nature or mankind. While the response of nature to such impacts is flexible in the way that all morphological changes with all the consequences are tolerated as part of the system, humanity cannot tolerate short-term or long-term changes without being threatened in its physical and economical existence. The objectives of this Advanced Research Workshop (ARW) on Environmentally Friendly Coastal Structures were: - to contribute to the critical assessment of existing knowledge in the field of coastal and environmental protection; - to identify directions for future research in that area; - to promote close working relationships between scientists from different countries and with different professional experience. The latest trends in research on coastal and environmental protection were summarized and developed during the meeting. Seventeen papers are presented in this book, attempting to cover all related aspects as completely as possible - coast, engineering structures, water, sediments, ecosystems in their complicated interaction.
Key-Notes -- Environmental Friendly Coastal Protection Structures the Endless Struggle of the Engineer Against Water, Waves and Erosion - Opening Address - -- Beach Nourishment: Benefits, Theory and Case Examples -- Innovations in Coastal Protection -- Classical, Innovative and Unconventional Coastline Protection Methods -- On the Stability of Rock Slopes -- Integrated Hydraulic-Environmental Modelling -- Interaction of Waves and Reef Breakwaters -- Coastal Protection and Associated Impacts - Environment Friendly Approach -- Selected Participant Presentations -- Numerical Simulations in Coastal Hydraulics and Sediment Transport -- Rehabilitation of Highly Protected Beaches by Using Environment-Friendly Structures -- Low-Crested Structures: Boussinesq Modeling of Waves Propagation -- Flow Measurements and Numerical Simulation on Low-Crested Structures for Coastal Protection -- Performance of Submerged Breakwaters as Environmental Friendly Coastal Structures -- Scour Development in Front of Coastal Structures at Intermediate Phases of Construction -- Cliff Erosion - How Much Do We Really Know about It -- Environmental Design and Monitoring of Large Submarine Outfalls: An Integrated Approach for Coastal Protection -- Evaluation of Coastal Defence Strategies in Portugal.
Keywords: ENGINEERING; CIVIL ENGINEERING; ENVIRONMENTAL SCIENCES; ENGINEERING; CIVIL ENGINEERING; ENVIRONMENT, GENERAL